2000
DOI: 10.1902/jop.2000.71.12.1821
|View full text |Cite
|
Sign up to set email alerts
|

Enamel Matrix Derivative in the Treatment of Human Intrabony Osseous Defects

Abstract: Treatment with flap surgery and EMD, compared to flap surgery with placebo, produced a significantly more favorable clinical improvement in intrabony periodontal defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
121
5
23

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(162 citation statements)
references
References 40 publications
(51 reference statements)
13
121
5
23
Order By: Relevance
“…This difference may be explained by several factors. In addition to a difference in patient populations, the mean value for baseline PD in the present study subjects ‫63.1ע82.7(‬ mm) was approximately 1 mm deeper than that ‫19.0ע33.6(‬ mm) reported by Okuda et al 15) . The CAL gain after regenerative periodontal treatment has been shown to be dependent on the initial PD; that is, the deeper the initial PD, the greater the PD reduction and CAL gain 5,16) .…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…This difference may be explained by several factors. In addition to a difference in patient populations, the mean value for baseline PD in the present study subjects ‫63.1ע82.7(‬ mm) was approximately 1 mm deeper than that ‫19.0ע33.6(‬ mm) reported by Okuda et al 15) . The CAL gain after regenerative periodontal treatment has been shown to be dependent on the initial PD; that is, the deeper the initial PD, the greater the PD reduction and CAL gain 5,16) .…”
Section: Discussioncontrasting
confidence: 77%
“…2). These values are slightly less than the ‫22.1מ‬ mm recession reported by Okuda et al 15) . A study by Sculean et al 20) demonstrated less recession at sites treated with EMD compared to guided tissue regeneration (GTR) treated sites.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Previous clinical trials have shown mean PPD reductions ranging from 3.3 to 4.3 mm for the EMP group and from 2.2 to 3.7 mm for the control group at an interval of 8 to 12 months after treatment. 3,7,10,13,19 In the present study, no significant differences in PPD reduction were observed between the EMP (3.7 mm) and OFD (4.0 mm) groups after 6 months. However, our results disagree with those of previ- ous studies that reported a significantly greater PPD reduction for the EMP group.…”
Section: Discussioncontrasting
confidence: 58%
“…5,15 These positive results in animals 17 were later confirmed by histological findings in humans 15 and by clinical improvement observed in controlled clinical trials. 3,7,8,10,13,19 Thus, the purpose of this study was to compare the results of periodontal clinical parameters after treatment of intrabony defects with open flap debridement (OFP) combined or not with enamel matrix protein (EMP).…”
Section: Introductionmentioning
confidence: 99%